Financial Literacy and Home Ownership: A Quantitative Analysis of the German Real Estate Market - Marotta, Gianfranco; Kröger, Sebastian; Zureck, Alexander (International Journal of Economics and Financial Issues, 2025)
Our work uses quantitative empirical analysis to examine the research question of whether a high level of financial literacy influences the purchase of real estate in Germany. Using a binary logistic regression analysis, a significant positive influence was identified based on a sample of 2,149 people. The average financial literacy of the group examined was 3.78 out of 5 points. It is striking that owners in the sample have a higher numeracy score (average: 3.92) compared to non-owners (average: 3.54). The result shows that the probability of owning a home, c. p., increases by 4.58 percentage points when the financial literacy score increases by one unit. Based on these results, policymakers are recommended to take action in order to develop a strategy to promote private pension provision in the form of home ownership.